5-Hydroxymethylfurfural formation and color change in lactose-hydrolyzed Dulce de leche. Issue 4 (November 2019) - Francisquini, Júlia d'Almeida; Rocha, Júlia; Martins, Evandro; Stephani, Rodrigo; Henrique Fonseca da Silva, Paulo; Toledo Renhe, Isis Rodrigues; Tuler Perrone, Ítalo; Fernandes de Carvalho, Antônio
Abstract: The work described in this Research Communication concerns the production of Dulce de leche (DL), that is a traditional product from South America obtained by concentration. Maillard reaction (MR) products are mainly responsible for the formation of color and flavor in this product. Lactose-hydrolyzed products have been developed to supply consumer demand, but this hydrolysis may affect the flavor, color, taste, texture and even some nutritional aspects of the product. We studied the influence of different levels of lactose-hydrolysis, sucrose addition and initial pH on the development of MR, appraised by the determination of 5-hydroxymethylfurfural (HMF). A process simulator with multi-monitoring system was used to produce 15 DL. Box-Behnken 3 3 experimental design was applied for the three factors: pH, lactose-hydrolysis level and sucrose concentration. Lipids, protein, ashes, carbohydrates, water activity, dissolved solids, colorimetric analysis and HMF (free and total) are among the physicochemical attributes and MR indicators analyzed in this work. The products showed significant differences in composition but all the values were in agreement with the literature. Moreover, higher levels of lactose hydrolysis and higher pH presented a direct relation with the development of MR, observed by an increase in coloration (lower luminosity) and more formation of HMF, both free and total. The present study expands the knowledge about DL spread made of lactose-hydrolyzed milk, allowing the food industries to produce a lactose free DL with nutritional and sensory characteristics closer to the traditional product.